Early analysis of software architecture to estimate energy consumption in android platform - Al Nidawi, Hasan Sajid Atta (2017)
Resource consumption of mobile applications (e.g. battery and data traffic) are still the primary concerns of mobile manufactures. It has been noted earlier that the consumption of a particular mobile application depends heavily on its software architecture. Therefore, mobile developers can make proper design decisions based on the comparative study performed on different software architectures. The idea of this research started through trying to find the evidence from literature on the consumption patterns of mobile applications. Consequently, we formulated the first objective which was to investigate the evidence related to the effectiveness of CP in android platform mobile applications. The results of this objective clarified the research importance which motivates us to move forward to the next objective which was to evaluate which approach, either SC architecture or MC architecture, is less energy-consuming in android mobile applications (DRCICS). This work presents three main approaches that are used in this research: Critical data analysis was performed using Systematic Literature Review (SLR); through the revision of the literature related to our research, quantitative data collection using mobile phone application was utilized for this purpose, and quantitative evaluating was done using SPSS: this approach was used in order to evaluate which approach, either SC architecture or MC architecture, is less energy-consuming in android mobile applications. The result of evaluation shows that MC architecture is less energy-consuming in android mobile applications in term of retrieval of data from the applied database, especially when the focus was on DRCICS. Such a fact discovered in the design phase is quite crucial for developers to be able to reduce resource consumption and hence increase the likelihood of success of their apps. These results provide useful guidelines for the developers in terms of energy consumption for the development of mobile applications needed to connect to remote or relational databases.